EMPOWERING COMMUNITIES THROUGH LIQUID ORGANIC FERTILIZER FOR COST AND NUTRITION GAINS IN CIBANTENG, BOGOR - Muna, Siti Umamah Naili; Rusdiyanto, Edi; Munawir, Abdillah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The main goal expected by the administrators of the Raharja Farmer Group is to achieve food security in Cibanteng Village. However, the skills related to organic vegetable cultivation and the availability of essential farming materials and tools such as seeds, organic fertilizer, pots, plastic containers, and others are still suboptimal. The community service method involved a series of discussions with representatives of the farmer group, including local residents, retired civil servants, and housewives. These discussions focused on the importance of organic vegetable cultivation techniques, the production of liquid organic fertilizer enriched with phytohormones, and the practical application of planting organic vegetables. Active participation from community members and intensive mentoring, both in person and via online platforms such as WhatsApp, significantly contributed to the success of the program. Residents successfully cultivated and harvested vegetables such as kangkung and pakcoy in their home gardens. This not only increased their organic vegetable consumption but also had a direct impact on reducing household expenses. The harvest enabled savings on vegetable purchases for up to one week and promoted household-level food independence. Evaluation results indicate that the program met the needs of the community partners and effectively reduced their reliance on local markets. Additionally, the use of shallot waste as liquid fertilizer improved soil fertility and ensured the quality of the organic crops. This success demonstrates the potential for long-term sustainability if managed properly through the institutional support of the farmer group.